Aggressive digital papillary adenocarcinoma – a rare malignant tumor of the sweat glands: two case reports and a review of the literature - Altmann S; Damert HG; Klausenitz S; Infanger M; Kraus A (Dove Medical Press, 2015)
Silke Altmann,1 Hans-Georg Damert,1 Stephanie Klausenitz,2 Manfred Infanger,1 Armin Kraus1 1Department of Plastic, Aesthetic and Hand Surgery, Otto-von-Guericke-University Magdeburg, 2Private Institute for Pathology, Magdeburg, Germany Abstract: Aggressive digital papillary adenocarcinomas are rare malignant tumors often located on the digits of the hand. Due to lack of pain, slow growth, and an inconspicuous appearance, diagnosis is often missed or delayed. We report two cases and review the present literature to give recommendations for diagnosis and treatment. Keywords: aggressive digital papillary adenocarcinoma, tumor, sweat glands